МОДЕРНИЗАЦИЯ КИТАЯ С ТРАДИЦИОННОЙ ДАНЬЮ К ПРОШЛОМУ (ҚазҰУ хабаршысы. Шығыстану сериясы, 2016)
Мақалада Қытай өркениетінiң қазiргi даму кезеңін-дегі идеологиясы және жаңғырту үдерістерінде Қытайелінің көне дәстүрлерінің ықпалы қарастырылады.This article examines the ideological line of the currentleadership, which is caused by a combination of modernculture and the finest achievements of traditional Chineseculture. Analyze the influence of the ancient traditions ofChina's current model of China's modernization.